Lipid droplets are dysregulated in the adult dentate gyrus during seizure. (28th October 2021) - Ahamad, A; Ge, S
Abstract: Introduction/Objective: Dentate gyrus (DG), a neurogenic niche, is a metabolically dense subregion of the hippocampus. Continuous production and integration of new neurons in the existing circuit and harmonious relationship between excitatory and inhibitory neurons accompanied by neuron-glia coupling is essential to maintain hippocampal homeostasis throughout adulthood. Imbalance in the neuronal activity generates seizures and can result in mesial temporal lobe epilepsy (MTLE). MTLE affects 50 million people across the globe and impairs the overall hippocampal network and its associated functions such as memory and cognition. Although altered lipid metabolism has been associated with status epilepticus, the role of lipid droplets (LDs), the minuscule metabolically active organelle known to provide a substrate for cellular energy, has not been explored in DG during seizure. LDs are composed of neutral lipids and surrounded by phospholipid monolayer, which is studded with a structural Perilipin family of proteins 1-5, reported to be involved in lipid metabolism. Methods/Case Report: To study LDs in the brain, we used a novel approach by injecting Bodipy, a lipid dye in the tail vein of mice, and successfully labeled LDs in the DG. We used the pilocarpine-induced seizure model. After Bodipy injection followed by seizure induction, mice were sacrificed at four time-points 0.5, 1-, 3- and 18 hours. Results (if a Case Study enter NA): We found a significant increase in Bodipy signal and Perilipin 4, LDs specific marker expression at four time-points post-seizure than in the control cohort. To elucidate the role of neuron-glia metabolic coupling in DG, we measured LDs in microglia and astrocytes and found a significant increase in LDs in seizure mice than control groups suggesting the role of glia in lipid regulation in DG. Conclusion: Overall, this novel study will highlight the undiscovered role of LDs in dentate gyrus during seizure and, in the future, can be used as a therapeutic target to alleviate the MTLE phenotype.